Comparison of Two High-Intensity Interval Training (HIIT) For Two Weeks on Fat Oxidation, Body Fat Percentage and VO2max in Overweight Young Males - Mehdi Gholizadeh; Mohammadreza Kordi; Ali Akbarnejad (Journal of Education and Community Health)
Background and Objectives: The purpose of this study was to determine the effect of 6 sessions of High Intensity Interval Training (HIIT) on fat oxidation, VO2max and body fat percentage in sedentary overweight young males. Materials and Methods: Overall, 16 inactive young males voluntarily participated in this study and were randomly divided to 2 Groups: Group A (HIIT-1) and Group B (HIIT-2). Two groups performed 3 HIIT sessions per week for 2 weeks. Group A (4 × 1 min /4 min R) and Group B (4×30s /2 min R) performed maximal sprint running within a 20 m area. Respiratory gas was collected 24 hours before and after the exercise protocol in a fasting state. Independent t test and paired t test were applied using the SPSS-18 software to analyze the data. Results: Statistical analysis showed that 6 sessions of HIIT led to an increase of 43% of fatty oxidation in Group A during the exercise test; these changes were significant compared to Group B (P <0.05). Changes in weight and body fat were significant in group A (P <0.05). Also, results showed a significant increase in VO2max in Group A (5.19%) and Group B (4%). Conclusions: According to the results of this study, it appears that 6 sessions of HIIT led to improvement of fatty oxidation and store glycogen. In conclusion, it appears that HIIT, in addition to reducing body fat and increasing aerobic fitness, is a time efficient means for decreasing weight and improving oxidation capacity in sedentary overweight young males.